Case Report: Role of Rotational Atherectomy in Complex PCI - Seprian Widasmara; Mohammad Saifur Rohman; Heny Martini; Indra Prasetya (Heart Science Journal, 2021)
Background : One in three patients undergoing percutaneous coronary intervention (PCI) exhibits moderate or severe coronary artery calcification. Coronary calcification remains a major independent predictor of PCI failure and adverse outcomes. PCI of calcified coronary lesions remains challenging, despite significant improvements in the available tools and techniques. Rotational Atherectomy (RA) is a critical component to improve PCI success in these situations by producing lumen enlargement by physical removal of plaque and reduction in plaque rigidity, thus facilitating dilationCase Illustration: A 73-year-old man with exertional angina was referred to our hospital, with a history of hypertension, diabetes mellitus, ex-smoker and dyslipidemia. Physical exam, electrocardiogram, chest x-rays, and laboratory findings were unremarkable, but transthoracic echocardiogram revealed anterior wall hypokinesis. History of cardiac catheterization outside of our center with angiographic result of left anterior descending (LAD) lesion, highly calcified, non-dilatable on first several POBA attempts. Coronary angiography at our center, revealed diffuse calcification from proximal to distal of the LAD artery with about 90% maximum stenosis in mid LAD. RA (Rotablator, Boston) was then performed with A 1.50 mm burr gradually advanced at 150,000 rpm to passed the lesion. After deployments of stents, final angiogram showed well positioned stents with good distal run-off flow. The patient was uneventful during the procedure and was discharged following day. Discussion: In experienced hands, RA is as safe as standard PCI. RA is as a tool to make PCI possible in complex lesions with moderate or severe calcification when clinical variables make PCI appropriate. Rotablator is a catheter-based interventional cardiology procedure using a high-speed rotational device designed to ablate atherosclerotic plaque and restore luminal patency. This help to facilitate stent delivery, avoiding the barotrauma caused by repeated high-pressure balloon inflations that can lead to vessel dissection or perforation. Atherectomy can be performed safely with optimal burr selection and proper ablation techniques, and as a result, complication rates have been significantly minimized, with few changes in the acute complications reported in contemporary studies. Keywords: percutaneous coronary intervention, calcified lesion, rotational atherectomy.